Ganges [ - Hugh-Jones, Tom; Rees, Dan (British Broadcasting Corporation, 2007)
A sumptuous series that tells the story of the most extraordinary river in the world. The Ganges runs through the heart of India. For millions of Hindus it is India's sacred river, but they share its banks with a rich varietyof wildlife.